TINJAUAN ETIKA BISNIS ISLAM TERHADAP PEMBATALAN AKAD JUAL BELI BAHAN BANGUNAN SECARA DROP ORDER OLEH PEMBELI DI TOKO TUNAS BARU KEC. BANDAR DUA KABUPATEN PIDIE JAYA (Analisis Terhadap Pembatalan Sepihak Dalam Konsep Jual Beli Salam) - Fikri Rijal (AL-ILMU, 2023)
This paper discusses the Review of Islamic Business Ethics Against the Cancellation of Sales and Purchases of Building Materials by Drop Order by Buyers at Tunas Baru Stores, Bandar Dua District, Pidie Jaya Regency (Analysis of One-sided Cancellations in the Salam Buy and Sell Concept). Buying and selling activities in everyday life inseparable from the desired needs. Even buying and selling itself is now inclined and can be developed according to the needs of the community, such as buying and selling building materials by DO which resembles the concept of a salam contract. This sale and purchase is a contract with the delivery of goods ordered by the seller at a predetermined time and the payment is made immediately by the buyer when the contract takes place. However, in practice, it sometimes causes unwanted things, such as unilateral cancellation by the buyer, as was the case in Bandar Dua District, Pidie Jaya Regency. The problem of this research is how are the implications and resolution of the cancellation of the sale and purchase contract by DO for building materials for the sellers and buyers and how is the review of Islamic Business Ethics towards unilateral cancellations made by the buyer in the sale and purchase contract of building materials by DO at the Bandar Dua Building Materials Store Pidie Jaya Regency. The method used is descriptive analysis method through primary data obtained from field research and secondary data obtained from library research. The results of the study show that the implications for the seller besides the loss are also profitable, as well as for the buyer who also benefits even though there is a loss. The unilateral cancellation in this case is according to a review of Islamic Business Ethics. Thus, the cancellation here becomes valid based on the settlement carried out by way of peace by the new Tunas shop, and there has been agreement between the parties who made the contract. So as to avoid any problems in the DO of these building materials.Keywords: Islamic Business, Buying And Selling Of Building Materials, Drop Order.